Commercially Available Rapid Methods for Detection of Selected Food-borne Pathogens. Issue 9 (3rd July 2016) - Valderrama, Wladir B.; Dudley, Edward G.; Doores, Stephanie; Cutter, Catherine N.
ABSTRACT: Generally, the enumeration and isolation of food-borne pathogens is performed using culture-dependent methods. These methods are sensitive, inexpensive, and provide both qualitative and quantitative assessment of the microorganisms present in a sample, but these are time-consuming. For this reason, researchers are developing new techniques that allow detection of food pathogens in shorter period of time. This review identifies commercially available methods for rapid detection and quantification of Listeria monocytogenes, Salmonella spp., Staphylococcus aureus, and Shiga toxin-producing Escherichia coli in food samples. Three categories are discussed: immunologically based methods, nucleic acid-based assays, and biosensors. This review describes the basic mechanism and capabilities of each method, discusses the difficulties of choosing the most convenient method, and provides an overview of the future challenges for the technology for rapid detection of microorganisms.